Population characteristics of A. Japonicus from the Kedah coastal waters of Peninsular Malaysia. - Arshad, Aziz; Nurul Amin, Sanker Mohammad; Y. L., Z. Nuradiella; Che Cob, Zaidi; Ara, Roushon; Aziz, D. (Asian Network for Scientific Information, 2012)
The study was an attempt to examine the size frequency distribution, length-weight relationship and morphometric variation of the Acetes japonicus from four different sides of Kedah coastal waters between March to May 2007 by using SPSS and PRIMER software. The average total length of the females from Batu Lintang and male of Tg. Dawai were the highest with the values of 17.07 and 13.93 mm, respectively. The growth co-efficient (b) values ranged between 2.0 to 4.0, indicating varieties of the growth pattern (negative allometric, isometric and positive allometric) for A. japonicus. The highest correlation of length-length relationship in female and male were found in the population of Kuala Sala. The morphological characteristics showed variation among populations. The highest similarity of morphometric characteristics was between Batu Lintang and Tg. Dawai for all groups (female, male, combined sexes).